Následky nerespektování práva ES při rozhodování českého soudu - Neubauer, Jindřich (2006)
Submitted diploma thesis deals with the theme of consequences of violation of EC law by a Czech court. The aim of this thesis is to evaluate the development of practice of the European court of justice which concerns this issue, and in particular those, which have an impact on national judiciary power.